2021
DOI: 10.1007/s11033-021-06569-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in the renin-angiotensin system and cognitive decline in Parkinson’s disease

Abstract: Background Renin-angiotensin system (RAS) influences the central nervous system not only through its peripheral impact—the brain possesses its own local RAS. Studies showed altered RAS components in Parkinson’s disease (PD) and their association with oxidative stress which may be linked to neurodegeneration and dementia. Moreover, the protective functions of RAS blockade antagonists against cognitive decline and dementia have been suggested. This study aimed to examine whether genetic variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
2
0
1
Order By: Relevance
“… 90 However, a cohort study on 256 PD patients showed no significant association between single nucleotide polymorphisms (SNPs) of RAS components with PD risk and cognitive impairment. 91 Though, these SNPs of RAS may affect the response and therapeutic efficacy of ACEIs and ARBs in PD patients. A meta‐analysis establish no significant connotation between ACE gene PD risks.…”
Section: Role Of Ras In Pdmentioning
confidence: 99%
See 1 more Smart Citation
“… 90 However, a cohort study on 256 PD patients showed no significant association between single nucleotide polymorphisms (SNPs) of RAS components with PD risk and cognitive impairment. 91 Though, these SNPs of RAS may affect the response and therapeutic efficacy of ACEIs and ARBs in PD patients. A meta‐analysis establish no significant connotation between ACE gene PD risks.…”
Section: Role Of Ras In Pdmentioning
confidence: 99%
“…A case–control study on 127 PD patients and 198 healthy controls showed that homozygote DD genotype of ACE gene was higher in PD patients compared to healthy controls 90 . However, a cohort study on 256 PD patients showed no significant association between single nucleotide polymorphisms (SNPs) of RAS components with PD risk and cognitive impairment 91 . Though, these SNPs of RAS may affect the response and therapeutic efficacy of ACEIs and ARBs in PD patients.…”
Section: Role Of Ras In Pdmentioning
confidence: 99%
“…RAS downregulation via ACE inhibitors or AT1R blockers has shown protective effects against cognitive impairment [ 140 ]. A recent clinical study found no associations between cognitive decline in PD and specific single nucleotide polymorphisms (SNPs) in genes encoding angiotensinogen, ATR1, ATR2, and ACE [ 141 ]. Furthermore, NLRP3 inflammasome gene variants have been associated with critical disease in COVID-19 patients, especially in men and older patients, as well as patients with diabetes type 2, hypertension, and a higher body mass index [ 142 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…(1) Receptor D1 . Whereas various investigations have failed to see any bipolar changes in the D1 receptor gene [ 71 , 72 ], a connection between polymorphism of the D1 receptor A48G and bipolar disease has been observed [ 73 , 74 ].…”
Section: Gpcrs and Mood Disordersmentioning
confidence: 99%